Acceptability of a parental early warning tool for parents of infants with complex congenital heart disease: a qualitative feasibility study. Issue 9 (22nd March 2018) - Gaskin, Kerry Louise; Wray, Jo; Barron, David J
Abstract : Aim: To explore the acceptability and feasibility of a parental early warning tool, called the Congenital Heart Assessment Tool (CHAT), for parents going home with their infant between first and second stage of surgery for complex congenital heart disease. Background: Home monitoring programmes were developed to aid early recognition of deterioration in fragile infants between first and second surgical stage. However, this necessitates good discharge preparation to enable parents to develop appropriate knowledge and understanding of signs of deterioration to look for and who to contact. Design: This was a longitudinal qualitative feasibility study, within a constructivist paradigm. Parents were taught how to use the CHAT before taking their infant home and asked to participate in semistructured interviews at four time points: before discharge (T0), 2 weeks after discharge (T1), 8 weeks after discharge (T2) and after stage 2 surgery (T3). Interviews were transcribed verbatim and thematically analysed. Setting: One tertiary children's cardiac centre in the UK. Subjects: Twelve parents of eight infants who were discharged following first stage cardiac surgery for complex congenital heart disease, between August 2013 and February 2015. Results: Four main themes emerged: (1) parental preparation and vigilance, (2) usability, (3) mastery, and (4) reassurance and support. Conclusions: The study highlighted the benefit of appropriately preparing parents before discharge, using the CHAT, to enable identification of normal infant behaviour and to detect signs of clinical deterioration. The study also demonstrated the importance of providing parents with information about when and who to call for management advice and support.